Effects of Evening Primrose Oil on Fibrocystic Breast Disease (Journal of Surgical Sciences, 2026)
Introduction: As the term implies, fibrocystic breast tissue can feel fibrous and cystic. Estrogen, progesterone and prolactin hormones directly affect the breast tissues by causing cells to grow and multiply. There are multiple modalities of treatment but no one is widely accepted. Evening primrose oil is an excellent source of the essential fatty acid, which may reduce swelling & pain of fibrocystic disease.Methods: Total 50 cases of clinically diagnosed fibrocystic breast disease were enrolled for study during August 2017 to August 2018. Sample was selected by purposive sampling technique. Data were collected from the patients and/or informant and recorded in structured case record form. Clinical examination and relevant investigations were done meticulously. At the first visit patients were treated by evening primrose oil. Then subsequent follow up conducted after 2 months and after 4 months of primary treatment to observe the effectiveness. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage.Result: Most common symptom was lumpiness and pain in the breast (76.0% & 46.0% respectively). Other manifestations were breast lump in 24.0%, relation with cycle in 88.0% of patients. At the first follow-up (2nd month), lumpiness in the breast, localize swelling and tenderness was improved (52.0%, 70.0% & 48.0% respectively), but breast lump remained unchanged in all patients. At the second follow-up (4th month) significant improvement occurred. Lumpiness in the breast present in 36.0% patients, pain in the breast in 22.0%, localize swelling in 48.0% and tenderness in 30.0% of patients. Mean verbal pain score at baseline was 5.3, following treatment pain was resolved/ decreased. At 2nd month VAS score was 3.8 and at 4th month VAS score was 3.1. Clinical improvements were subjectively assessed by the patients after completing of the treatment. Subjective evaluation or patient satisfaction corresponded to 76.0% improvement.Conclusion: In this study our experience showed that evening primrose oil can be prescribed at fibrocystic breast disease patients, as this shows high rate to relief of symptoms.Journal of Surgical Sciences 2023;27(2): 41-45